Persepsi motivasi mahasiswa dalam minat investasi green sukuk berdasarkan gender - Shinta Alifia Fahira; Whedy Prasetyo; Hendrawan Santosa Putra (Akuntansi dan Teknologi Informasi, 2024)
Research was conducted to investigate the motivational perspectives of scholars regarding investing in Green Sukuk based on gender concepts. This concept provides meaning for scholar investment decision-making in carrying out investment strategies. Qualitative methods with a phenomenological approach were employed in this research. The findings revealed that both male and female scholars are motivated to invest in Green Sukuk. These motivations align with the values of environmental preservation, reducing greenhouse gas emissions, the potential for high returns, safe investments guaranteed by the government, and the fact that this investment can avoid usury. Green Sukuk is also perceived as a means to invest surplus funds. Males are more inclined in Green Sukuk due to environmental concerns, while females are attracted by the investment security it offers. This can be explained by the findings that males tend to have higher environmental awareness compared to females, whereas females are more inclined to avoid investments with high risks. Hence, females are more cautious in their investment choices. However, when examining investment decision-making, there are no differences between males and females except in terms of income.